Impacto das necessidades psicológicas básicas mediadas pelo relacionamento treinador-atleta na experiência esportiva de jovens atletas brasileiros - Pizzo, Gislaine Contessoto (2016)
The objective of the study was to analyzed the impact of basic psychological needs mediated by the coach-athlete relationship in the sports experience of young Brazilian athletes. Participated 355 athletes, male and female, with a mean age of 16,07 ± 0,82 years, from the final phase of the Brazilian Youth School Games of 2015. As instruments were used the Youth Experience in Sport Scale (YES-S), Coach-Athlete Relationship Questionnaire (CART-Q) and the Basic Needs Satisfaction in Sport Scale (BNSSS). The data analyzes were performed in the statistical package SPSS version 20.0, using the Kolmogorov Smirnov, Mann-Whitney test and Spearman correlation, adopting p<0,05. Analyzes involving Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were performed in AMOS software version 20.0. The results showed that the Brazilian young athletes showed higher averages for closeness (CAR), autonomy (BPN) and initiative (SE). When compared according to the type of the sport, athletes of group sports presented higher perception of complementarity (p=0,032) (CAR), and greater experiences for personal and social skills (p=0,017) (SE), whereas athletes of individual sports, presented higher satisfaction of the competence (BPN) (p=0,002). Based on gender, female athletes obtained higher levels of closeness (p=0,001) (CAR), and cognitive abilities (p=0,044) (SE), while male athletes were more satisfied in the competency (BPN) (p=0,002). Regarding the correlation between CAR, BPN and SE, it highlight positive relationships between commitment and relationship (r=0,28); relationship and cognitive abilities (r=0,26); commitment to cognitive skills and initiative (r=0,25) and closeness to initiative and goal setting (r=0,25). When analyzing the model, the results evidenced significant relations between BPN satisfaction and coach-athlete relationship (r²=0,25) and CAR significantly mediated the relation between BPN satisfaction and sports experiences (r²=0,19). It was still possible to emphasized that the direct effect of BPN on SE was β=0,27, and when CAR was inserted as mediator, this effect increased in β=0,12 resulting in a total effect of β=0,39. It is concluded that in the Brazilian sport context, young athletes satisfied with their basic psychological needs are more likely to establish good relationships with their coaches. In addition, the social relations between motivated athletes and coaches have a significant impact on athletes sports experiences, contributing to a greater sports engagement.